Managing Information / Certificate in Management Studies: First Edition - Gardner John; Ramsden John; Centre For Management, University Of York (2000)
Introduction, Types of Information, Sources of Information, Acquiring Information, Analysing and Evaluating Information, Recording and Storing Information, Dissemination Channels, Appendix.
Introduction, Types of Information, Sources of Information, Acquiring Information, Analysing and Evaluating Information, Recording and Storing Information, Dissemination Channels, Appendix.